Hate Inc. : why today's media makes us despise one another - Taibbi, Matt (OR Books, 2019)
Provides an insider's guide to the variety of ways today's mainstream media tells us lies. Part tirade, part confessional, Taibbi reveals that what most people think of as "the news" is, in fact, a twisted wing of the entertainment business. In the Internet age, the press have mastered the art of monetizing anger, paranoia, and distrust. Taibbi, who has spent much of his career covering elections in which this kind of manipulative activity is most egregious, provides a taxonomic survey of American political journalism's dirty tricks. --From publisher description